METHODOLOGICAL PROBLEMS OF MONITORING IN RESEARCH OF NATURAL ECOLOGICAL SYSTEMS IN THE CONDITIONS OF FORMATION OF AGROCENOSIS - Veronika Razmikovna Svechkareva; Dilnoza Saifutdinovna Anarkulova (Modern American Journals, 2025)
This article examines ways to address methodological issues in studying natural ecological and natural-technical systems with the goal of identifying the most effective methods for obtaining information that supports measures for the rational use of natural resources and environmental protection.
Keywords: Ecological and natural-technical systems, ecological functions, natural resources